Life Cycle Reliability and Maintenance Analyses of Wind Turbines. (March 2017) - Chan, Daniel; Mo, John
Abstract: Wind power generation is an effective form of clean, renewable energy which operate both on land and offshore. The primary means of converting wind to power is by wind turbines. The issue with wind turbines is the life cycle reliability, operation and maintenance tasks associated. Frequent premature failures resulting in reactive maintenance can be costly which results in downtime and loss of production. Currently, prognostic health management is conducted on wind turbines by a supervisory control and data acquisition system. However, using this approach, only reactive and preventative maintenance is being utilised. This paper analyses life cycle reliability and maintenance of wind turbines which applies the concept of failure mode and effects analysis (FMEA) and bond graph modelling to simulate the effects of maintenance strategies on the life cycle cost of wind turbines. To ensure wind turbines life cycle reliability, the components failures would occur in sync with the biannual maintenance. This will ensure effective use of resources, such as transportation and personnel costs, associated with the maintenance action. Preventative maintenance can also be conducted in accordance to the MTTF values.